Evaluation of babassu meal in feed for layer hens during the growth phase - Carneiro, Mif; Sakomura, Nk [UNESP]; Malheiros, Eb [UNESP]; Araújo, Ja [UNESP]; Silva, Ep Da [UNESP]; Kawauchi, Im [UNESP]; Fernandes, Jbk [UNESP]; Sousa, Jrst De (Fundação APINCO de Ciência e Tecnologia Avícolas, 2014)
Studies were conducted to evaluate the nutritional value and inclusion levels of babassu meal (BM) in the diet of grower layer pullets in substitution to wheat meal. Digestibility, metabolism and growth trials were conducted. Twelve cecectomized roosters were used in the digestibility assay to determine the coefficients of standardized digestibility of amino acids (CSDAA). The metabolism trial was conducted with 30 adult roosters to determine the apparent metabolizable energy corrected for nitrogen (AMEn) of BM. A growth trial was performed to determine replacement levels of wheat midds by BM diet using 360 six-week-old commercial layer pullets. BM was included at the 0, 75 and 150 g/kg of BM, during grower and development rearing phases, respectively. Feed intake, body weight gain, and feed conversion were evaluated. BM AMEn was determined as 1,474 kcal/kg, on as-fed basis. The CSDAA determined for BM were below 88% for all AA. The inclusion of BM in the feed of grower layers (7-18 week) significantly decreased feed intake (p < 0.05), but significantly improved body weight gain and feedconversion ratio (p < 0.05) at 15% inclusion level. Considering the nutritional value and performance results, BM can replace wheat midds in diets of grower layer pullets.
Keywords: Alternative feedstuff; Nutritional composition; Digestibility; Performance